2016
DOI: 10.1021/acs.inorgchem.6b01427
|View full text |Cite
|
Sign up to set email alerts
|

2-(Methylamido)pyridine–Borane: A Tripod κ3-N,H,H Ligand in Trigonal Bipyramidal Rhodium(I) and Iridium(I) Complexes with an Asymmetric Coordination of Its BH3Group

Abstract: The complexes [M(κ(3)-N,H,H-mapyBH3)(cod)] (M = Rh, Ir; HmapyBH3 = 2-(methylamino)pyridine-borane; cod = 1,5-cyclooctadiene), which contain a novel anionic tripod ligand coordinated to the metal atom through the amido N atom and through two H atoms of the BH3 group, were prepared by treating the corresponding [M2(μ-Cl)2(cod)2] (M = Rh, Ir) precursor with K[mapyBH3]. X-ray diffraction studies and a theoretical Quantum Theory of Atoms in Molecules analysis of their electron density confirmed that the metal atoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 80 publications
(42 reference statements)
1
17
0
Order By: Relevance
“…The observation of one band at 2083 cm À1 for the stretching mode of the cyanidol igand and two bands at 1922 and 1871 cm À1 for the CO stretching mode of the carbonyl ligands in the IR spectrum of 3b-CN are in agreement with ac yanido dicarbonyl complex. The connectivity in 3b-CN wasfinally con- (2);P4-B1-P5 112.28 (8),P3-Fe1-P6 93.03(1),P 1-Fe1-P2 71.31(1), H1Fe1-Fe1-C1177.2 (9).…”
Section: Phosphine-stabilized Borylene Versus Boratementioning
confidence: 99%
See 2 more Smart Citations
“…The observation of one band at 2083 cm À1 for the stretching mode of the cyanidol igand and two bands at 1922 and 1871 cm À1 for the CO stretching mode of the carbonyl ligands in the IR spectrum of 3b-CN are in agreement with ac yanido dicarbonyl complex. The connectivity in 3b-CN wasfinally con- (2);P4-B1-P5 112.28 (8),P3-Fe1-P6 93.03(1),P 1-Fe1-P2 71.31(1), H1Fe1-Fe1-C1177.2 (9).…”
Section: Phosphine-stabilized Borylene Versus Boratementioning
confidence: 99%
“…Neutral phosphine‐boranes are best described as Lewis acid/base adducts (R 3 P→BH 3 ) that consequently have been used as ligands in transition metal complexes since the 1980s . Recently, they have attracted attention as potential hydrogen‐storage materials, metal‐free catalysts and ambiphilic ligands …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, while the M-H200 and M-H300 interactions are equivalent in complex 1, they are different in complex 2. As it has been previously shown that the Shimoi and the agostic attachments of a B-H bond to a metal atom have similar electron density at the M-H bcp (ρ b ) and similar Laplacian of the electron density at the M-H bcp (∇ 2 ρ b ), but different ellipticity at the bcp (ε b ), that of agostic-type being significantly greater than that of 14,22 the data given in Table 3 indicate that the type of interaction existing between the M atom of 1 and 2 and the borane B-H bonds is intermediate between those of Shimoi and agostic types and that, in complex 2, the interaction of the B-H200 bond with the Ru atom is more agostic than that of the B-H300 bond.…”
mentioning
confidence: 93%
“…1), 14 which are the first metal complexes derived from 2-(methylamino)pyridine-borane (HmapyBH 3 ). In solution at room temperature, the BH 3 group of these complexes rotates about the B-N bond averaging the three B-H 14 The analytical and spectroscopic data of the ruthenium complex 2 confirmed its composition and the presence of one hydride, one phosphane, one CO, and one mapyBH 3 ligand, but they did not help to unambiguously assign the ligand positions, which were subsequently determined by XRD (see below).…”
mentioning
confidence: 99%